The vanishing American adult : our coming-of-age crisis--and how to rebuild a culture of self-reliance - Sasse, Benjamin E. (St. Martin's Griffin, 2018)
"In an age of safe spaces, trigger warnings, and political upheaval, America's kids are getting some bad ideas--and adults are not doing enough to redirect them. Most importantly they are not helping them build the scar tissue that is the foundation of character. Many of the coming-of-age rituals that have defined the American experience since the Founding--learning the the value of work, leaving home to start a family, becoming economically self-reliant--are being delayed or skipped entirely. The statistics are daunting: a third of all 18- to 34-year-olds live with their parents and most kids over 13 are spending more than 60 percent of their waking hours consuming media. From these various phenomena, U.S. senator Ben Sasse of Nebraska, who as president of a Midwestern college observed the trials of this generation up close, sees an existential threat to the American way of life. In The Vanishing American Adult, Sasse diagnoses the reasons that this generation can't grow up and offers a path for raising children to become active, engaged citizens. He identifies core experiences for all young people to pursue and parents to encourage--working hard to appreciate the benefits of labor, traveling to understand deprivation and want, building a personal library for exposure to new ideas, and nurturing physical health to develop discipline"--Publisher's description